Increased number of retinal vessels in acromegaly. Issue 3 (March 2020) - Füchtbauer, Laila; Olsson, Daniel S; Coopmans, Eva C; Bengtsson, Bengt-Åke; Norrman, Lise-Lott; Neggers, Sebastian J C M M; Hellström, Ann; Johannsson, Gudmundur
Abstract : Objective: Excess of growth hormone (GH) and insulin-like growth factor 1 (IGF-1), as in acromegaly, is associated with increased risk of diabetes, but whether retinal vessels are altered is unknown. The aim of this study was to evaluate retinal vessel morphology in patients with acromegaly at diagnosis and after treatment and to describe the prevalence of diabetic retinopathy in patients with long-standing acromegaly and diabetes. Design: Two independent observational studies, one being prospective and the other retrospective and cross-sectional. Methods: Retinal vessel morphology of 26 patients with acromegaly was examined at diagnosis and 1 year after treatment and compared to 13 healthy controls. Cross-sectional evaluation of 39 patients with long-standing acromegaly and diabetes was performed. Fundus photographs were digitally analyzed for vessel morphology. Results: Patients with acromegaly had a median (interquartile range) of 34.3 (30.0–39.0) vessel branching points compared to 27.0 (24.0–29.0) for healthy controls ( P  < 0.001). Tortuosity of arterioles and venules remained unchanged. Vessel morphology did not change significantly after treatment. Patients with acromegaly and diabetes for a median of 14 years also had a high number of branching points (34.2 (32.5–35.6)), but the prevalence of diabetic retinopathy was not higher than expected in diabetic patients without acromegaly. Conclusions: Patients with acromegaly have an increased number of vascular branching points in the retina without an alteration of macroscopic vessel morphology. This is consistent with an angiogenic effect of GH/IGF-1 in humans. The prevalence of diabetic retinopathy was not increased in patients with acromegaly and diabetes.